THE FUNCTION OF ΑNCIENT GREEK IN MODERN GREEK – POLISH LEGAL TRANSLATION TEACHING - GORTYCH, Karolina (Comparative Legilinguistics, 2009)
According to ideas which have been presented in main course books and methodological guides, a lack of Ancient Greek in the process of teaching Modern Greek Philology has occurred. It could be a problem if Modern Greek philologists decide to be translators and interpreters of legal texts because the Greek language of law has archaisms, rigid structures and elements. My project deals with the function and amount of Ancient Greek in the curiculume of studies of Modern Greek Philology. I conclude that it is impossible to avoid Ancient Greek in the curriculum of Modern Greek Philology completely. I show the necessity of the Ancient Greek language because present Greek grammar and dictionaries cannot offer any insight in this field. Analysis of the curriculum affects the Modern Greek Language and Literature Department at Adam Mickiewicz University. The research material concludes with selected parts of Greek and Cypriot statutory acts which also affect the aforementiones issues.